2009
DOI: 10.1002/eji.200839010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid release of cytoplasmic IL‐15 from tumor‐associated macrophages is an initial and critical event in IL‐12‐initiated tumor regression

Abstract: This study reveals that the IL-15 rapidly released into serum upon IL-12 injection into tumor-bearing mice is critical for the subsequent leukocytic infiltration of the tumor and tumor-bearing tissue. The increase in serum IL-15 occurs within 2 h after IL-12 injection concomitantly with a decrease in cytoplasmic IL-15 in tumor-associated M/ (TAM). Injection of anti-IL-15 one hour prior to IL-12 abrogates subsequent leukocytic infiltration into the tumor and prevents the IL-12-induced reduction of primary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…TAMs are considered an attractive target for therapeutic intervention. These proposed strategies include activation of TAMs to a tumoricidal state (17)(18)(19), repression of the tumor-supportive activities of TAMs (20), and depletion of TAMs (21)(22)(23). A recent animal study showed that overexpression of PEDF in a rat prostate tumor by transient transfection of a PEDF-expressing plasmid caused increased macrophage recruitment and expression of inducible nitric-oxide synthase in macrophages (12).…”
Section: Pigment Epithelium-derived Factor (Pedf)mentioning
confidence: 99%
“…TAMs are considered an attractive target for therapeutic intervention. These proposed strategies include activation of TAMs to a tumoricidal state (17)(18)(19), repression of the tumor-supportive activities of TAMs (20), and depletion of TAMs (21)(22)(23). A recent animal study showed that overexpression of PEDF in a rat prostate tumor by transient transfection of a PEDF-expressing plasmid caused increased macrophage recruitment and expression of inducible nitric-oxide synthase in macrophages (12).…”
Section: Pigment Epithelium-derived Factor (Pedf)mentioning
confidence: 99%
“…In addition to direct induction of T, NK, and NKT cell cytotoxicity, IL-12 also promotes macrophage activity via T-and NK-cell-produced IFN [1]. Several studies demonstrated that macrophage activation is critical to the antitumor eVects of this cytokine [2][3][4][5]. SpeciWcally, intratumoral delivery of IL-12 was shown to induce a rapid switch in tumor-associated macrophage (TAM) phenotype from M2 to M1 and release of IL-15, a cytokine that was found to be essential to T-and NK-cell recruitment, and tumor kill [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that macrophage activation is critical to the antitumor eVects of this cytokine [2][3][4][5]. SpeciWcally, intratumoral delivery of IL-12 was shown to induce a rapid switch in tumor-associated macrophage (TAM) phenotype from M2 to M1 and release of IL-15, a cytokine that was found to be essential to T-and NK-cell recruitment, and tumor kill [5]. The role of direct macrophage cytotoxicity in post-IL-12 tumor regression on the other hand is less well deWned [3].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages play a highly important role in carcinogenesis, starting from transformed cell control, contributing to tumor initiation by chronic inflammation, and supporting tumor growth and metastasis (1). This high versatility of macrophages and their important role in various diseases prompted researchers worldwide to investigate the possibilities of therapeutic targeting of macrophages or even their use in cell-based therapies (5)(6)(7). Strong arguments in favor of therapeutic targeting of macrophages is provided by recent findings made by us and others demonstrating high levels of macrophage functional plasticity (5,8,9).…”
mentioning
confidence: 99%